PENGARUH JUMLAH WAJIB PAJAK TERDAFTAR DAN PENERBITAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK PENGHASILAN PADA KPP PRATAMA MALANG UTARA - Diyah Anisa; Nur Diana; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2021)
Taxes are mandatory contributions paid by the people to the state without direct contribution and will be used in the interests of the government and the general public (Mardiasmo: 2011). According to Law Number 6 of 1983 as last amended by Law Number 28 of 2007 concerning General Provisions and Tax Procedures, it is stated that "Taxes are mandatory contributions to the state that are owed by private persons or entities that are compelling under the Law, with does not get direct compensation and is used for the state's needs for the greatest prosperity of the people ”. Income Tax (PPh) is a type of tax whose collection system uses the Self Assessment System and has the largest contribution in state revenue from the tax sector. Income Tax (PPh) is a tax imposed on tax subjects on the income they receive or earn in a tax year. Realization of tax revenue for 2018 amounted to Rp1,315.9 trillion or grew up to 14.3% and in 2019 amounted to Rp1,545.3 trillion or grew by 5.05%. Tax revenue in Indonesia has increased every year which is intended to finance national development and support the progress of the country (Ministry of Finance, 2019. Keywords: the number of registered taxpayers, issuance of compulsory letters